Investigating Causing Relation earning per share and Future Return to Existing Rational Intrinsic Bubble of Listed Companies in Tehran Stock Exchange - مهسا فرخنده; محمد حسن قلی زاده; اسماعیل رمضانپور (مطالعات تجربی حسابداری مالی, 2016)
Considering the important role of stock market in economic development, finding this fact that whether price increases is due to fundamental elements or not can help a country’s policy makers to direct the capital market to right direction.Therefore, this study investigates the existence of a certain type of rational bubbles due to the fundamental elements which called rational intrinsic bubble during 1385 to 1392. Then in second phase this matter will be examine that if the earnings can predict future return regarding to intrinsic bubbles so for this purpose Vector Auto Regression model has been applied .Required data have been collected seasonally and calculated by using and Rahavard novin software, 65 companies selected as research samples and data has been analyzed by using Eviews7 .the analyzing results indicate that there are intrinsic bubbles in 15 companies which is due to changing of fundamental elements such as dividend. Also results indicate that in companies in which there is not any intrinsic bubbles,earning can predict future returns.